Implementation of E-Learning Learning in Bengkulu City Learning Activities SKB - Ismawati, Dwi (VISI : Jurnal Ilmiah Pendidik dan Tenaga Kependidikan Pendidikan Non Formal, 2023)
This study aims to describe E-learning learning at the SKB (Learning Activity Center) in Bengkulu City. This study uses a qualitative method with a descriptive approach. The results of this study are that E-learning at the SKB (Learning Activity Center) in Bengkulu City is still new, so managers must socialize it to learning residents. The learning process is carried out with the Google Classroom application by providing lots of material to learning residents. Constraints in the learning process are less effective in achieving the expectations of learning residents because sometimes learning residents who have committed to take part in online learning using Google Classroom often do not submit assignments, do not open accounts that have been given, the difficulty in this implementation is that many learning residents do not have a signal when the learning process so the assignments given are often delayed in the task collection process. In addition, the E-learning that is implemented at the SKB SPNF City of Bengkulu also makes it easy for some of the learning residents who work while studying, the learning residents are helped by this learning method so that when there is free time they can re-read the material provided on the Google account. that class.